Assessment of hiatus defect size in hiatal hernia patients using computed tomography - Gür Özcan, Seray Gizem; Zengin, Nezih; Bilir, Burak; Kaçmaz Kat, Nurcan; Durak, Doğukan (The European Research Journal, 2024)
Objectives: The aim of this study is to investigate the hiatus defect diameter by measuring on multi-detector computed tomography images in hiatal hernia patients. Methods: The multi-detector computed tomography images of 50 patients and 50 individuals in control group included in this study were investigated. The hiatus surface area (cm²), hiatus antero-posterior and transverse diameters (cm), and the thickness of both diaphragmatic crura (mm) were measured by reformatting contrast-enhanced thoraco-abdomino-pelvic computed tomography images using the region of interest method. Results: In this study, a significant difference was obtained among groups according to hiatus surface area, hiatus antero-posterior, and transverse diameter measurements, and both left and right diaphragmatic crural thickness measurements (P